Embedding Safety in Design (SiD) within Construction Contract Law: Challenges and Opportunities for Improved Safety Outcomes: Proactive Risk Mitigation: Strengthening Construction Safety Through Design Integration - Knobel, Nicola (New Zealand Journal of Health and Safety Practice, 2025)
This paper explores the integration of Safety in Design (SiD) into construction contract law, with a focus on improving safety outcomes and risk management across New Zealand, Australia, and the United Kingdom. By examining case studies and legislation such as New Zealand's Health and Safety at Work Act (HSWA) 2015, this research identifies the challenges and opportunities in embedding SiD principles within construction contracts. Key challenges include regulatory vagueness, liability concerns, and economic barriers, while opportunities lie in proactive risk management, collaboration, and the use of emerging technologies like Building Information Modeling (BIM). The paper offers recommendations to strengthen regulatory frameworks, enforce SiD through construction contracts, and enhance safety collaboration. The findings highlight the transformative potential of SiD in shifting safety management from reactive measures to proactive risk mitigation in the design phase, aiming to improve safety and minimise legal disputes in the construction industry.